Peran Psikologi Dalam Meningkatkan Pembelajaran Siswa - zahra, Zaitun; Adiliani, Zahrina Farizah; Fatrah, Fatrah; Faelasup, Faelasup (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
Abstract Psychology plays an important role in the world of education, namely in advancing the quality of education so that it becomes even better and in accordance with the goals of education, namely bringing students to change for the better, both in behavior and in knowledge. The aim of this research is to determine the role of psychology in improving student learning. The results obtained by researchers show that there are 5 roles of psychology in improving student learning, including: 1) psychology helps educators understand individual differences, such as learning styles and cognitive abilities, 2) provides insight into student motivation, which will later be used as an incentive for students to learn , 3) helps develop student learning skills, such as study skills, problem solving, and cognitive skills, 4) helps students to manage their emotions, and also 5) plays an important role in developing student measurement and evaluation. This research uses qualitative methods with data collection techniques through library research, where the results obtained will be explained in descriptions and illustrations.